Access to optically enriched α-aryloxycarboxylic esters via carbene-catalyzed dynamic kinetic resolution and transesterification - Liu, Bin (2021)
Optically active α-aryloxycarboxylic acids and their derivatives are important functional molecules. Disclosed here is a carbene-catalyzed dynamic kinetic resolution and transesterification reaction for access to this class of molecules with up to 99% yields and 99:1 er values. Addition of a chiral carbene catalyst to the ester substrate leads to two diastereomeric azolium ester intermediates that can quickly epimerize to each other and thus allows for effective dynamic kinetic resolution to be realized. The optically enriched ester products from our reaction can be quickly transformed to chiral herbicides and other bioactive molecules.